Determinan Self-Efficacy Wirausaha terhadap Intensi Wirausaha di Kota Banda Aceh (Jurnal Riset Manajemen dan Akuntansi, 2025)
This research aims to test and analyze the influence of self-efficacy determinants on entrepreneurial intentions, reviewing role models, need for achievement, subjective normal. This research method uses a quantitative approach. The total sample for this research was 100 respondents. Samples are determined using the Slovin formula. Sample collection used probability sampling techniques with the Proportionate Stratified Random Sampling type. Hypothesis testing uses multiple linear regression analysis at a confidence level of 95% (α = 0.05). The results of this research are that role models partially have a significant effect on entrepreneurial intentions. Need for achievement partially influences entrepreneurial intentions. Subjective norms have a significant effect on entrepreneurial intentions. Simultaneously, role models, need for achievement and subjective norms have a significant effect on entrepreneurial intentions.